THE EFFECT OF STUDENTS’ MATHEMATICAL DISPOSITION ON MATHEMATICAL CRITICAL THINKING ABILITY OF ELEMENTARY SCHOOL STUDENTS - Arifuddin, Ahmad; Wahyudin, Wahyudin; Prabawanto, Sufyani (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2023)
Abstract: This study investigates the effect of students' mathematical dispositions on elementary school students' mathematical critical thinking abilities. The existing problems are related to low critical thinking skills and poor mathematical disposition of students, including low curiosity, low ability to ask questions during the mathematics learning, and poor ability to provide logical reasons for communicating ideas. This research was quasi-experimental, where the participants in this study amounted to 49 5th-grade students in two integrated Islamic elementary schools in Cirebon City, Indonesia. Data was collected through a questionnaire of students' mathematical disposition and a test of mathematical critical thinking ability. The data analysis employed descriptive statistical analysis and simple regression analysis. The research found that the students' mathematical disposition significantly affects elementary school students' mathematical critical thinking ability. The significance value is significant (sig. 0.000 <0.05) with a correlation coefficient of 0.597. The results also reveal that students with a high level of mathematical disposition perform better in mathematical critical thinking ability than students with medium and low mathematical dispositions. So, it can be concluded that the mathematical disposition influences students' mathematical critical thinking abilities. Abstrak: Penelitian ini bertujuan untuk menginvestigasi pengaruh disposisi matematis siswa terhadap kemampuan berpikir kritis matematis siswa sekolah dasar. Dengan adanya permasalahan terkait rendahnya kemampuan berpikir kritis dan disposisi matematis siswa yang kurang baik, seperti rasa ingin tahu yang rendah, kemampuan bertanya ketika proses belajar matematika yang rendah serta kemampuan memberikan alasan yang logis dalam mengkomunikasikan ide-ide yang kurang. Penelitian ini merupakan penelitian kuasi eksperimen. Partisipan dalam penelitian ini berjumlah 49 siswa kelas 5 di 2 (dua) sekolah dasar Islam terpadu di Kota Cirebon, Indonesia. Data dikumpulkan melalui angket disposisi matematis dan tes kemampuan berpikir kritis matematis. Sementara itu, data hasil penelitian dianalisis melalui analisis statistik deskriptif dan analisis regresi sederhana. Hasil penelitian menunjukkan bahwa disposisi matematis siswa berpengaruh signifikan terhadap kemampuan berpikir kritis matematis siswa sekolah dasar. Nilai signifikansinya sebesar sig. 0.000 < 0.05 dengan koefisien korelasi 0.597. Hasil penelitian juga mengungkapkan bahwa siswa yang memiliki level disposisi matematis tinggi, kemampuan berpikir kritis matematisnya lebih baik dibandingkan dengan siswa yang memiliki level disposisi matematis sedang dan rendah. Sehingga dapat disimpulkan bahwa disposisi matematis berpengaruh terhadap kemampuan berpikir kritis matematis siswa.